Moral Education for Students to Address Juvenile Delinquency - Uni Khoerotun Rizkiyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study uses a qualitative approach, so that the main instruments in this study are educators, students, and schools. The instruments that the author uses in collecting data in the field according to the object of discussion in this study are the author conducting observations and documentation. Teachers have some responsibility to provide moral education, when children are at school to teachers at school. There is no need to see which family the child is entrusted to. Teachers are the second parents of students at school. As parents at school, teachers should be responsible for the development of their students in terms of cognitive, affective and psychomotor. Moreover, teachers focus more on instilling moral education so that students avoid juvenile delinquency which is basically usually done by teenagers the same age as students such as those at MTs Darun Nahwi Singajaya. Regarding morals or good examples, Allah SWT has given a description of the morals of the Prophet Muhammad SAW. Because in life, a human being since birth always does and acts, thinks, feels, feels and relates to others.